2022
DOI: 10.1021/acs.jpca.2c04611
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nanostructures Accessible to an Organic Surfactant Atmospheric Aerosol Proxy

Abstract: The composition of atmospheric aerosols varies with time, season, location, and environment. This affects key aerosol properties such as hygroscopicity and reactivity, influencing the aerosol’s impact on the climate and air quality. The organic fraction of atmospheric aerosol emissions often contains surfactant material, such as fatty acids. These molecules are known to form three-dimensional nanostructures in contact with water. Different nanostructures have marked differences in viscosity and diffusivity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 74 publications
(197 reference statements)
1
25
0
Order By: Relevance
“…We carried out a systematic study of the phase-composition relationship for the oleic acid–sodium oleate system in both bulk mixtures and levitated droplets . The addition of compounds commonly co-emitted with oleic acid such as sugars (glucose, fructose, and sucrose) and a saturated fatty acid (stearic acid) altered the observed LLC phase. , In some instances, a difference in the sugar added meant the difference between an inverse hexagonal phase (opaque and directionally dependent diffusion) and a close-packed inverse micellar phase (viscous and translucent). More complex mixtures informed by atmospheric measurements and with up to 6 components mostly returned the inverse hexagonal and close-packed inverse micellar LLC phases.…”
Section: Qualitative Indications Of the Atmospheric Importance Of Llc...mentioning
confidence: 99%
See 3 more Smart Citations
“…We carried out a systematic study of the phase-composition relationship for the oleic acid–sodium oleate system in both bulk mixtures and levitated droplets . The addition of compounds commonly co-emitted with oleic acid such as sugars (glucose, fructose, and sucrose) and a saturated fatty acid (stearic acid) altered the observed LLC phase. , In some instances, a difference in the sugar added meant the difference between an inverse hexagonal phase (opaque and directionally dependent diffusion) and a close-packed inverse micellar phase (viscous and translucent). More complex mixtures informed by atmospheric measurements and with up to 6 components mostly returned the inverse hexagonal and close-packed inverse micellar LLC phases.…”
Section: Qualitative Indications Of the Atmospheric Importance Of Llc...mentioning
confidence: 99%
“…34−36 Recent fieldwork has demonstrated that the trans form of oleic acid, elaidic acid, authors suggested that the steric arrangement for elaidic acid would be similar to that for saturated fatty acids, which are known to crystallize to form solid or semisolid phases. 3 The formation of viscous phases in aerosol particles may provide an explanation for this observation. The oleic acid−ozone reaction is therefore an ideal candidate for the studies we present here due to this discrepancy and the abundant literature for comparison.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Laboratory studies of the air–water interface demonstrate surface adsorption of H 2 O 2 , as well as determining the structure of hydroxy organic acids of varying size at the interface . Additional work addresses adsorption–desorption of semivolatile VOCs on mineral surfaces, and reactive uptake of HgO and a recently discovered dimethyl sulfide oxidation product (hydroperoxymethyl thioformate) on aerosols of various compositions. , The effects of aerosol properties on ice nucleation and on the partitioning of semivolatiles, , the effects of pH on organosulfate structures in the condensed phase, and the accessibility of various nanostructures for surfactants on atmospheric aerosol proxies are also reported. Wilson, Willis, and co-workers , provide model frameworks for trace gas uptake and reaction in aerosol or microdroplets, and for multiphase ozonolysis reactions.…”
mentioning
confidence: 99%